Car4U transportation service - Modern technology based alternative ride solution for passengers to travel across Malaysia - Ahmad Dahlan, Abdul Rahman; Mohammad Musleh, Islah; Mohammad Shafiq, Saleh (Research Publish Journals, 2017)
With the emergence of technology integration and long-existent complaints from passengers and taxi drivers, demands for alternative ride services have seen a momentum in many urban cities. This article proposes a new technology based car rental business model, Car4U, to serve passenger go anywhere and anytime they want either having their own car or ask for a driver to get them to their destination in Malaysia. Car4U offer car with driver and without driver to passengers who do not own any car or want someone else to drive for them. Car4U also provides opportunity for people who want drive only or give car for rent for a period of time to earn money. Car4U aim is to facilitate travellers and commuters who want to commute and travel daily from one place to other. Besides that customers can request for a ride or car using Car4U app or website.